American Creoles : The Francophone Caribbean and the American South - Britton, Celia; Munro, Martin (Book collections on Project MUSE., 2012)
The Francophone Caribbean and the American South are sites born of the plantation, the common matrix for the diverse nations and territories of the circum-Caribbean. This book takes as its premise that the basic configuration of the plantation, in terms of its physical layout and the social relations it created, was largely the same in the Caribbean and the American South. Essays written by leading authorities in the field examine the cultural, social, and historical affinities between the Francophone Caribbean and the American South, including Louisiana, which among the Southern states has had a quite particular attachment to France and the Francophone world. The essays focus on issues of history, language, politics and culture in various forms, notably literature, music and theatre.